SARS-CoV-2 Omicron Variant: Exploring Healthcare Workers' Awareness and Perception of Vaccine Effectiveness: A National Survey During the First Week of WHO Variant Alert - Temsah, Mohamad-Hani; Aljamaan, Fadi; Alenezi, Shuliweeh; Alhasan, Khalid; Alrabiaah, Abdulkarim; Assiri, Rasha; Bassrawi, Rolan; Alhaboob, Ali; Alshahrani, Fatimah; Alarabi, Mohammed; Alaraj, Ali; Alharbi, Nasser S.; et al. (Frontiers in Public Health, 2022)
Background As the SARS-CoV-2 Omicron variant spreads in several countries, healthcare workers' (HCWs) perceptions and worries regarding vaccine effectiveness and boosters warrant reassessment. Methods An online questionnaire among HCWs in Saudi Arabia (KSA) was distributed from Dec 1st−6th 2021 to assess their perceptions, vaccine advocacy to the Omicron variant, and their perception of the effectiveness of infection prevention measures and vaccination to prevent its spread, their Omicron variant related worries in comparison to the other variants, and their agreement with mandatory vaccination in general for adults. Results Among the 1,285 HCW participants, two-thirds were female, 49.8 % were nurses, 46.4% were physicians, and 50.0% worked in tertiary care hospitals. 66.9% considered vaccination to be the most effective way to prevent the spread of the Omicron variant and future variants. The respondents however perceived social distancing (78.0%), universal masking (77.8%), and avoiding unnecessary travel (71.4%) as slightly superior to vaccination to prevent the spread of SARS-CoV-2 variants. HCWs aging 55 or older agreed significantly with vaccine ineffectiveness to control Omicron spread, while those who believed in non-pharmacological infection prevention measures agreed significantly with vaccination for that purpose. Male HCWs had a significant agreement with mandatory vaccination of all eligible adult populations. On the other hand, unwilling HCWs to receive the vaccine had strong disagreements with mandatory vaccination. Conclusions The current study in the first week of Omicron showed that only two-thirds of HCWs felt that vaccination was the best option to prevent the spread of the Omicron variant, indicating the need for further motivation campaigns for vaccination and booster dose. HCWs had a strong belief in infection prevention measures to contain the spread of SARS-CoV-2 variants that should be encouraged and augmented.